“Diberi air gula… awalnya nangis menjadi diam, karena kenyang, gak lemas, daya tahan tubuhnya meningkat”; Studi Pola Asupan pada Bayi - Mila Syahriyatul Maghfiroh; Agung Dwi Laksono (Amerta Nutrition, 2020)
Background: Babies were vulnerable to health and nutrition problems. WHO states that 60% of deaths of children under five were caused by malnutrition. Of these, two-thirds of them were caused by improper feeding of babies. Objective: to describe patterns of food intake in infants in Kepung Village, Kediri District.Methods: The study was designed qualitatively with an ethnographic approach. Data collection was performed using in-depth interviews and participatory observation. The study was conducted in Kepung Village, Kediri, East Java. The process of collecting data was done by researchers by staying with the target for 6 months. Results: The pattern of intake in infants aged 0-6 months in Kepung Village was not only given breast milk but was given food in the form of formula milk, sugar water and ‘kepok’ banana. When the mother or caregiver feels that the baby was still hungry, it will be given food intake other than the milk. The practice of feeding was inseparable from the influence of hereditary belief, where sugar water was believed to make the baby not fussy because the baby becomes full and healthy. Conclusion: The pattern of intake in infants in Kepung Village was very varied. Not only breast milk, babies have also been given mashed up adult food. People in Kepung Village also have a habit of giving their babies sugar water. ABSTRAKLatar Belakang: Bayi adalah masa yang rentan terhadap masalah kesehatan dan gizi. WHO menyatakan bahwa 60% kematian anak balita disebabkan oleh keadaan kurang gizi. Dari jumlah tersebut, dua per tiga diantaranya disebabkan oleh pemberian makan yang kurang tepat.Tujuan: Penelitian ditujukan untuk menggambarkan pola asupan pada bayi di Desa Kepung, Kabupaten Kediri.Metode: Studi didesain secara kualitatif dengan pendekatan etnografi. Pengumpulan data dilakukan dengan menggunakan metode wawancara mendalam dan observasi partisipatif. Studi dilakukan di Desa Kepung, Kecamatan Kepung, Kabupaten Kediri, Jawa Timur. Proses pengumpulan data dilakukan oleh peneliti dengan tinggal bersama target. Peneliti lived in di lokasi penelitian selama 6 bulan.Hasil: Pola asupan pada bayi usia 0-6 bulan di Desa Kepung tidak hanya diberikan ASI saja, tapi diberikan makanan berupa susu formula, air gula dan pisang kepok. Praktik pemberian makanan tersebut tidak terlepas dari pengaruh kepercayaan yang turun-temurun, yang mana air gula diyakini dapat membuat bayi tidak rewel karena bayi menjadi kenyang dan menyehatkan.Kesimpulan: Pola asupan pada bayi di Desa Kepung sangat bervariasi. Tidak hanya ASI, bayi juga sudah diberi makanan orang dewasa yang dilembutkan. Masyarakat di Desa Kepung juga memiliki kebiasaan memberikan bayinya air gula.